The state of knowledge regarding pertussis amongst young adults - Borowski, Bartosz; Kupisz, Zuzanna; Długosz, Patrycja; Kozioł, Małgorzata (Journal of Education, Health and Sport, 2022)
Pertussis remains a serious health problem to this day. Even though a successful vaccine campaign reduced the morbidity rate in most countries, it still is a present and concerning disease. The sickness is especially dangerous to infants and young children, as it may result in serious health complications, and even death. The aim of this study was to determine how much do young adults know about this condition, and how often does pertussis occur within this population, as well as within its family members. Materials and methods: data was collected with use of an authorial survey, which was handed around a group of 201 freshmen medical students in contact, in April 2022. Results: Most of the students possess basic knowledge regarding aetiology, routes of transmission and symptoms of pertussis, but lack information about the vaccines, treatment, course of the disease and specific at-risk groups. Some students were diagnosed with the condition in the past, and some have a family member diagnosed with it sometime. Conclusion: Young adults have basic knowledge regarding pertussis, but they should be educated about some aspects of this sickness, with use of social campaigns or advertisements. Only some of the people are affected by pertussis during their life, as the disease is relatively rare in developed countries. A possibility of getting a booster shot of pertussis vaccine should be touted.